2020
DOI: 10.1177/0333102420906843
|View full text |Cite
|
Sign up to set email alerts
|

Have the IHS Guidelines for controlled trials of acute treatment of migraine attacks been followed? Laying the ground for the 4th edition

Abstract: Background The International Headache Society (IHS) has published four editions of Guidelines for acute clinical trials in migraine in the past 28 years. This continuous update process has been driven by the increasing amount of scientific data in the field of migraine and by the need to continuously improve the quality of trials. Objectives To illustrate: i) the results of the analysis on the adherence of published trials to the 3rd edition published in 2012, in order to identify the critical areas that neede… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Similar scoring methods have been used in the past to examine trial adherence to specific IHS guidelines. [5][6][7] Although many of the recommendations outlined in the original IHS guideline have remained unchanged (double-blind, placebo-controlled, randomized, etc. ), some recommendations show discrepancies between editions.…”
Section: Data Extraction and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Similar scoring methods have been used in the past to examine trial adherence to specific IHS guidelines. [5][6][7] Although many of the recommendations outlined in the original IHS guideline have remained unchanged (double-blind, placebo-controlled, randomized, etc. ), some recommendations show discrepancies between editions.…”
Section: Data Extraction and Analysismentioning
confidence: 99%
“…5 Additionally, Alpuente et al reviewed the adherence of trials to the third edition of the Guidelines for acute treatment of migraine. 6 They identified migraine-specific and end-point-related recommendations that deserve special attention and found that some guideline recommendations were not thoroughly followed. Investigations such as these are valuable in providing a better understanding of study quality and important groundwork for developing future editions of the IHS Guidelines for controlled trials of acute treatment of migraine .…”
Section: Introductionmentioning
confidence: 99%
“…Given the centrality of endpoint choice, research consensus regarding outcome measures has been surprisingly difficult to achieve. Surveys of the literature consistently show that less than half of published clinical trials adhere to guidelines developed by the International Headache Society in 1991, updated in 2000, 2012, and again in the last 2 years 1–3 . This finding may suggest that the recommended outcomes and endpoints do not serve the needs of a substantial percentage of researchers.…”
mentioning
confidence: 99%